The Effect of Plasma Triglyceride-Lowering Therapy on the Evolution of Organ Function in Early Hypertriglyceridemia-Induced Acute Pancreatitis Patients With Worrisome Features (PERFORM Study): Rationale and Design of a Multicenter, Prospective, Observational, Cohort Study - Cao, Longxiang; Zhou, Jing; Chen, Mingzhi; Chen, Tao; Liu, Man; Mao, Wenjian; Lin, Jiyan; Hong, Donghuang; Yao, Weijie; Sun, Yi; Qin, Kaixiu; Guo, Feng; et al. (Frontiers in Medicine, 2021)
Background: Acute pancreatitis is a potentially life-threatening inflammatory disease with multiple etiologies. The prevalence of hypertriglyceridemia-induced acute pancreatitis (HTG-AP) had been increased in recent years. It is reported that early triglyceride (TG) levels were associated with the severity of the disease, and TG lowering therapies, including medical treatment and blood purification, may impact the clinical outcomes. However, there is no consensus regarding the optimal TG-lower therapy, and clinical practice varies greatly among different centers. Our objective is to evaluate the TG-lowering effects of different therapies and their impact on clinical outcomes in patients with predicted severe HTG-AP. Methods: This is a multicenter, observational, prospective, cohort study. A total of approximately 290 patients with predicted severe HTG-AP are planned to be enrolled. The primary outcome is organ failure (OF) free days to 14 days after enrollment. Secondary outcomes include new-onset organ failure, CT severity score, level of TG, ICU free days to 14 days after enrollment, 60-day mortality, etc. Generalized linear model (GLM), Fine and Gray competing risk regression, and propensity score matching will be used for statistical analysis. Discussion: Results of this study will reveal the current practice of TG-lowering therapy in HTG-AP and provide necessary data for future trials. Clinical trial registration: Registered at https://www.chictr.org.cn/index.aspx. Trial registration number: ChiCTR2000039541